Energy Analysis in the Production of Purple Sweet Potato Crackers - Renny Eka Putri; Melia Elius Putri Gurning; Ifmalinda Ifmalinda; P.A Oktavionry (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The production process of purple sweet potato (PSP) crackers involves several stages, including peeling, washing, boiling, kneading, grinding, cutting, frying, and packaging. This study aims to analyze the energy flow and production costs associated with each stage of processing sweet potatoes into crackers at the Azizah Crackers Production House in Padang City. The types of energy considered in this study included human labor, fuel gas, electricity, and raw materials (PSP, cooking oil, and supporting materials). Results showed that the total input energy for the production of PSP crackers was 784,629.95 kJ with average output energy of PSP crackers 803,880.00 kJ. The energy output of PSP crackers was 1.02 times the energy input. The cutting and frying activity required the largest input energy of 46.18% (362,310.15 kJ), while packaging activity required the smallest energy of 0.38% (2,992.33 kJ). Based on the energy type, raw materials contribute the largest energy, amounted to 85.83% (674,822.86 kJ), and the smallest type of energy was electrical energy, which was 0.74% (5,839.72 kJ). Keywords: Energy consumption. Energy flow, Production costs, Production process, PSP Crackers.